Correlation between electron-phonon coupling and superconductivity of Sn2+ ion irradiated MgB2-thin films. Issue 12 (15th June 2023) - Pham, Ha H.; Le, Tien; Nguyen, The Nghia; Nam, Nguyen Hoang; Nguyen, Nhung T.; Sohn, Min Kyun; Kang, Dae Joon; Park, Tuson; Yun, Jinyoung; Lee, Yeonkyu; Kim, Jeehoon; Tran, Duc H.; et al.
Abstract: This study investigates the impact of 2 MeV Tin ion (Sn 2+ ) irradiation with doses from 2E12 to 7E13 on the Raman spectroscopy and superconductivity properties of MgB2 -thin films samples. Raman spectroscopy has been used to examine the behavior of electron-phonon coupling (EPC). For the superconductivity properties, the temperature dependence resistivity, R(T), and the magnetic field-dependent magnetization, M(H), were measured. The import of EPC, which is related to the change in critical temperature (Tc ), was calculated using the McMillan-formula modified by Allen–Dynes, using the phonon frequency of the middle peak center ω2 (E2g ). Raman spectroscopy showed that the value of EPC decreased from 1.113 (Pristine) to 0.969 (7E13). Although the critical temperature (Tc ) decreased with increasing Sn 2+ ion doses, the values of the in-field critical current density (Jc ) and upper critical field (Hc2 ) increased and reached a maximum for the 5E13 sample. In addition, the magnetic penetration depths of the pristine and optimal dose (5E13) samples were measured using magnetic force microscopy (MFM), providing the thermodynamic critical field (Hc ) in the MgB2 films.